The reality of Awqaf and its investment in the Republic of Gambia: An applied jurisprudence study / Karamo Ibrahima Saidykhan - Karamo Ibrahima , Saidykhan (2022)
The legitimate aim of the institution of waqf in Islam is for the religious and social interest. Failing which in performing its duty a waqf will not be able to achieve this aim. This is the case in the Republic of the Gambia in which the waqf face many obstacles and problems due to many factors such as lack of real estate registration and documentation of endowment properties, leasing for less than the customary rate, no proper lease contract, late payment of lease, absence of the official administrative staff and lack of religious understanding among the people in dealing with waqf property. These have led the waqf in The Republic of the Gambia going in to ruin and unproductive . This study aimed to get acquainted closely with these problems and to propose solutions from fiqh point of view. In this study, the researcher took (a) the inductive method by referring to the literatures on waqf to get acquainted with the law of waqf, (b) the historical approach to trace back the history of waqf in Gambia, and (c) the descriptive analytical approach to analyze the problems and issues at hand and to come out with the solutions. The study found that waqfs in the Republic of The Gambia have not been optimally exploited, vulnerable to mismanagement and corrupted, the limited mode of generating incomes to renting and below market rate, adhering to the clasiccal fiqh with the absence of a supervisory role and the mechanisms of investment. The researcher suggest in this study of honouring the sanctity of waqf and setting up investment and administrative control mechanisms, taking into account the fiqh point of views, so as to capable of overcoming problems.